Upland and field fowl, its involvement in the bacterial infections - Liakh, Yuriy G. (Journal of the Belarusian State University. Ecology, 2019)
The article considers the questions of population characteristics of upland and field fowl in hunting farms of Belarus. The data of their numbers, and habitats and features are presented. The characteristic of these species in terms of hunting and their role in the epizootic well-being of Belarus.